2004
DOI: 10.1097/01.mlr.0000109126.50398.5a
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Burnout and Patient Satisfaction

Abstract: Improvements in nurses' work environments in hospitals have the potential to simultaneously reduce nurses' high levels of job burnout and risk of turnover and increase patients' satisfaction with their care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
640
3
44

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 728 publications
(714 citation statements)
references
References 41 publications
27
640
3
44
Order By: Relevance
“…Studies have indicated that control over nursing practice is associated with increased job satisfaction and improved patient outcomes 1,34,36 and with decreased job-related stress, burnout, and staff turnover. 37,38 The association between less autonomy and increased nurses' intentions to resign, along with decreased job satisfaction, is in accordance with previous findings 2 and emphasizes the importance of exercising autonomy in some aspects of nursing work. Although low clinical decision-making autonomy has been reported among Hellenic intensive care nurses, 16 the levels of autonomy in our study are difficult to compare with the levels in previous studies because of differences in the instruments used.…”
Section: Discussionsupporting
confidence: 79%
“…Studies have indicated that control over nursing practice is associated with increased job satisfaction and improved patient outcomes 1,34,36 and with decreased job-related stress, burnout, and staff turnover. 37,38 The association between less autonomy and increased nurses' intentions to resign, along with decreased job satisfaction, is in accordance with previous findings 2 and emphasizes the importance of exercising autonomy in some aspects of nursing work. Although low clinical decision-making autonomy has been reported among Hellenic intensive care nurses, 16 the levels of autonomy in our study are difficult to compare with the levels in previous studies because of differences in the instruments used.…”
Section: Discussionsupporting
confidence: 79%
“…The issue of working conditions of the nursing staff has already been mentioned for a long time in the specialised literature. Many researchers indicate that the working conditions and number of nurses or their exposure to stress factors have a significant impact on the safety of a patient [28,29]. Not all changes in the environment and working conditions of nurses must be connected with financial expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Added to this, associations between nurse stress and job performance [22][23][24], quality of care [25,26] and patient safety [27,28] have been established. Yet despite this evidence base, it is recognised that further work is needed to improve our understanding of the effects of stress (and burnout) on patient safety in nursing [29,30].…”
Section: Consequences Of Stress In Nursingmentioning
confidence: 99%